Forced distance learning at a Russian technical university: A comparative analysis of key challenges assessment - N. A. Lukianova; J. O. Okhorzina; T. V. Konyukhova; O. N. Kiselev (Образование и наука)
Introduction. On the example of a technical university, the article presents a comparative analysis of assessments of key difficulties identified among the faculty during the transition to distance learning in the spring of 2020 and 2022 throughout the COVID-19 pandemic. The authors identified trigger challenges, which do not lose relevance in the context of the recurrence of a pandemic (and not only) and a person’s ability to adapt to the situation. Generalised recommendations are proposed to compensate for the influence of socio-psychological and communicative barriers to improve the quality of teaching activities of the faculty mediated by information and communication technologies.Aim. The presents paper aims at conducting a comparative analysis to assess key challenges, which are determined by the human factor and affect the implementation of the educational process by the lecturers during distant work with students.Methodology and research methods. The analysis was carried out during spring semesters 2020 and 2022 amid the realisation of forced distance learning. The authors used the methods of scientific and theoretical analysis, synthesis; empirical collection of a dataset of 2 cross-sectional studies using a questionnaire, the C. Rogers & R. Diamond SPA test, and the social stratification level test. Two respondent pools included 307 lecturers from Tomsk Polytechnic University. The results were processed by comparative analysis and using the SPSS 26.0 statistical package program for social sciences.Results. The comparative analysis of the results in two pools showed that the key challenges were: 1) socio-psychological challenges associated with frustration, the challenge for adapting to the remote implementation of the educational process due to the certain disorientation and unprepared teachers; 2) communicative barriers related to the complexity of keeping students’ attention and reducing the quality of materials, the necessity for lecturers to have special communicative skills that meet the conditions of remote work (linguistic, subject, discursive, pragmatic, socio-cultural, technical), and supraprofessional competencies necessary when working in conditions different from traditional methods of teaching. It is concluded that the prerequisites for successful distance learning are determined by the presence of digital educational platforms and hardware resources for their implementation, and by the socio-psychological training of the faculty. In this regard, the authors made the recommendations on the organisation of consistent systematic work by the university personnel service in terms of organising teacher training in the specifics to work in a remote format from the point of view of not only technological (acquisition of skills to develop electronic courses, introduce types of tasks focused on interactive, group collaboration, gamification elements, fractional materials and their visualisation, etc.), but also the psychological acceptance of the situation, the development of emotional competence, adaptability, socio-psychological stability, as well as the improvement of communicative competence that meets today’s challenges.Scientific novelty and practical significance. The comparative analysis in dynamics revealed that the socio-psychological and communication barriers do not lose significance and influence on the lecturers, despite the repeatability of situations associated with a sharp transition in the implementation of the educational process from the traditional to the remote format. There is, therefore, a need for comprehensive work of the university HR service to compensate for the identified difficulties and build a trajectory for the consistent preparation of the faculty for the likely repetition of the situation with the forced distance learning, since the risk of its repetition due to a pandemic, a change in geopolitical or other conditions, is high enough. The implementation of the proposed recommendations for building a vector of readiness for remote work will reduce the negative socio-psychological impact of stressors and improve the quality of the educational process.